Intranuclear characteristics of pig oocytes stained with brilliant cresyl blue and nucleologenesis of resulting embryos - Murin, Matej; Strejcek, Frantisek; Bartkova, Alexandra; Morovic, Martin; Benc, Michal; Prochazka, Radek; Lucas-Hahn, Andrea; Pendovski, Lazo; Laurincik, Jozef (Zygote (Cambridge, England), 2019)
Brilliant cresyl blue (BCB) vital labelling is a powerful method for analyzing the quality of porcine cumulus-oocyte complexes. Our aim was to investigate the correlation between the selection of porcine oocytes using BCB labelling and selected intranuclear characteristics of porcine oocytes and parthenotes. Moreover, BCB labelling was correlated with the diameter of the oocyte and the developmental potential of the parthenotes. The following methods were used: BCB labelling, measurement of the diameter of the oocyte, parthenogenetic activation, immunocytochemistry, transmission electron microscopy, enucleation and relative protein concentration (RPC) analysis. We determined that the diameter of the oocytes in the BCB-positive (BCB+) group was significantly larger than in the BCB-negative (BCB-) group. Immediately after oocyte selection according to BCB labelling, we found significant difference in chromatin configuration between the analyzed groups. BCB+ oocytes were significantly better at maturation than BCB- oocytes. BCB+ embryos were significantly more competent at cleaving and in their ability to reach the blastocyst stage than BCB- embryos. Ultrastructural analyses showed that the formation of active nucleoli in the BCB+ group started at the 8-cell stage. Conversely, most BCB- embryos at the 8-cell and 16-cell stages were fragmented. No statistically significant difference in RPC in nucleolus precursor bodies (NPBs) between BCB+ and BCB- oocytes was found. We can conclude that BCB labelling could be suitable for assessing the quality of porcine oocytes. Moreover, the evaluation of RPC indicates that the quantitative content of proteins in NPB is already established in growing oocytes.
Keywords: prasata; Swine; blastocysta; embryo savčí; oocyty; Cell Nucleus; konfokální mikroskopie; Brilliant cresyl blue; Intranuclear characteristics; Cell Size; velikost buňky; Embryo, Mammalian; jaderné proteiny; buněčné jádro; reprodukovatelnost výsledků; Reproducibility of Results; Microscopy, Confocal; Animals; Oxazines; ženské pohlaví; Microscopy, Electron, Transmission; Pig; zvířata; barvení a značení; Nucleoli; oxaziny; Staining and Labeling; Female; Blastocyst; Nuclear Proteins; Nucleologenesis of embryos; transmisní elektronová mikroskopie; Oocytes